Familiy Quality of Life: Framework, Assessment and Intervention - Almudena FERNÁNDEZ GONZÁLEZ; Delfín MONTERO CENTENO; Natxo MARTÍNEZ RUEDA; José Ramón ORCASITAS GARCÍA; María VILLAESCUSA PERAL (Siglo Cero, 2015)
This paper offers an approach to recent literature on Family Quality of Life, underlining relevant features for framing and guiding assessment and intervention practices, both for practitioners and organizations for people with intellectual and development disabilities. This work is a part of a larger project that has been developed in a collaborative way by authors and professionals serving families in GORABIDE (Biscay Association Supporting People with Intellectual Disabilities), funded by the Biscay Province Council. Most of this text was analyzed and discussed with GORABIDE’s staff. Some questions we have tried to answer here are: what does scientific literature says about Family Quality of Life’s conceptual framework and dimensions?, what factors do usually influence it?, what are the most frequent models and instruments for assessment and intervention with families?